2007
DOI: 10.1007/bf02913326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum zinc level and plasma SOD activity in senile cataract patients under oxidative stress

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
5
15
0
Order By: Relevance
“…It was suggested that SOD activity was more sensitive to zinc rather than cadmium exposure. Similar results were also reported in other organisms previously (Olin et al 1995;Chakraborty et al 2007). Perhaps it could be explained that zinc was an essential component of copper/zinc SOD, and addition of external zinc was convenient to stabilize copper/zinc SOD and enhance SOD enzyme activity (Kajihara et al 1988;Jing et al 2007).…”
Section: Discussionsupporting
confidence: 84%
“…It was suggested that SOD activity was more sensitive to zinc rather than cadmium exposure. Similar results were also reported in other organisms previously (Olin et al 1995;Chakraborty et al 2007). Perhaps it could be explained that zinc was an essential component of copper/zinc SOD, and addition of external zinc was convenient to stabilize copper/zinc SOD and enhance SOD enzyme activity (Kajihara et al 1988;Jing et al 2007).…”
Section: Discussionsupporting
confidence: 84%
“…10 In our study MDA is the indicator of lipid peroxidation, which is significantly elevated (P<0.001) when compared with controls suggesting that increased MDA and lipid peroxidation may be considered as indicators of senile cataract formation. Similar observations also made by Babizhayer MA et al 11 Donma et al 4 Renu Garg et al 12 Indranil chakraborthy et al 13 Zehra Hashim and Shanshad Zarina. 14 The lipid peroxides are responsible for the formation of cataract and also cataract causes increased lipid peroxidation levels, thus the development of a vicious cycle involving cataract, cell damage, and lipid peroxides is involved in the pathology of the lens.…”
Section: Resultssupporting
confidence: 76%
“…SPD ϭ surfactant protein D decreased levels of serum superoxide dismutase 3 in the COPD group compared with the control group and are in agreement with those of Zeng et al, 50 Gavali et al, 51 and Tavilani et al 52 This decreased activity in subjects with COPD probably results from an increase in consumption of antioxidants. 53 We found a superoxide dismutase 3 levels of 244.79 Ϯ 69.12 U/L in the control group (see Table 4), whereas Chakraborty et al 54 reported plasma superoxide dismutase levels of 4.06 Ϯ 0.26 U/mL, KoturStevuljevic et al 55 found plasma superoxide dismutase levels of 153 Ϯ 36 U/L in non-coronary heart disease control subjects, and Comhair et al 56 reported a mean serum superoxide dismutase level of 2.75 U/mL. These differences may be due to differences in measurement methods.…”
Section: Discussionmentioning
confidence: 59%